Pemanfaatan Prinsip Personalisasi Belajar dalam Pembelajaran Daring pada Mata Kuliah Designing E- Learning - Meidiani Elsandra Pratiwi; Kunto Imbar; Dewi S. Prawiradilaga (Universitas Negeri Jakarta, 2022)
The utilization of learning personalization principles in online learning for Designing E- Learning Course intended to create a personalize online course by utilizing the principles invented by Margaret Martinez and David A Wiley on Instructional Use of Learning Object book. In which its application represented in Designing E- Learning course. This research is applying Rapid Prototyping method consisting of 5 main stages which are: Assess Needs and Analyse Content; Set Objectives; Construct Protoype; Utilize Protoype; Install and Maintain System, that are only conducted to install without maintain system. This research has been reviewed by instructional designer expert with score 3.8, instructional media expert with score 3.6, and materials expert for Designing E- Learning course with score 3.8, in which each review received “Very Well” credit with minor adjustment needed. The review from users also received a “Very Well” credit with average score is 3.73